2003
DOI: 10.1046/j.1365-2370.2003.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B*15 subtypes in the population of north‐eastern Thailand

Abstract: The HLA-B*15 group is the most polymorphic HLA-B allele and so has several subtypes. These subtypes have not been defined in the population of north-eastern Thailand (NET). In a previous study, using polymerase chain reaction-sequence-specific primers (PCR-SSP), subtypes were categorized into four groups, namely: group I: HLA-B*15 (01, 04-07, 12, 14, 19, 20, 24, 25, 26N, 27, 32, 33, 34 and 35); group II: HLA-B*15 (02, 08, 11, 15, 28 and 30); group III: HLA-B*1503/4802; group IV: HLA-B*1521. Groups I and II occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Another study reported a positive association with HLA-B*1502 in 98% of 60 Han Chinese patients with the adverse drug reaction compared to 4% of patients who did not have the reaction [152,153]. Similar associations have been reported for other Asian populations, despite variability in the frequency of HLA-B*1502 in those populations (Figure 6.2) [155][156][157][158][159]. Similar associations have been reported for other Asian populations, despite variability in the frequency of HLA-B*1502 in those populations (Figure 6.2) [155][156][157][158][159].…”
Section: Pharmacogenomics In Psychiatric Disorderssupporting
confidence: 64%
“…Another study reported a positive association with HLA-B*1502 in 98% of 60 Han Chinese patients with the adverse drug reaction compared to 4% of patients who did not have the reaction [152,153]. Similar associations have been reported for other Asian populations, despite variability in the frequency of HLA-B*1502 in those populations (Figure 6.2) [155][156][157][158][159]. Similar associations have been reported for other Asian populations, despite variability in the frequency of HLA-B*1502 in those populations (Figure 6.2) [155][156][157][158][159].…”
Section: Pharmacogenomics In Psychiatric Disorderssupporting
confidence: 64%
“…Some predominant alleles in Chinese were rare in Wa such as A*0207 (0.8%), B*4601 (0.4%), and B*5502 (0.8%). On the other hand, rare alleles in the other populations showed high frequencies in Wa including A*3303 (16.0%), B*1532 (11.8%), and DRB1*1504 (13.4%): B*1532 was only reported in Thai and DRB1*1504 was in Chinese Dai [40,41]. In addition several hapoltypes were only found in Wa including A*1101-B*1532-DRB1*1504 (8.8%), A*1101-B*3501-DRB1*1404 (5.1%), and A*3303-B*3503-DRB1*1301 (4.6%).…”
Section: Discussionmentioning
confidence: 94%
“…A high prevalence of 5% is also seen in Asians residing in North America. 32 The HLA-B ⁄ 1502 is one of the most common HLA-B alleles among Thai, 33 Burmese, 34 Vietnamese 35 and Western Javanese 36 but is rare in Caucasians. In a prior study of European populations, the allele frequency was only 1% to 2%.…”
Section: Current Explanationsmentioning
confidence: 99%